Three‐dimensional high‐resolution T1 and T2 mapping of whole macaque brain at 9.4 T using magnetic resonance fingerprinting. Issue 6 (7th February 2022) - Gu, Yuning; Wang, Lulu; Yang, Hongyi; Wu, Yun; Kim, Kihwan; Zhu, Yuran; Androjna, Charlie; Zhu, Xiaofeng; Chen, Yong; Zhong, Kai; Yu, Xin
Abstract: Purpose: Quantitative T1 and T2 mapping in non‐human primates with whole‐brain coverage is challenged by the requirement of sub‐millimeter resolution and the inhomogeneity of the transmit magnetic field (B1 + ) covering a large field of view. The goal of the current study is to develop a magnetic resonance fingerprinting (MRF) method for simultaneous T1 and T2 mapping of the entire macaque brain within feasible scan time. Methods: A three‐dimensional (3D) MRF sequence with both inversion‐ and T2 ‐preparation modules was developed and evaluated on a 9.4 T preclinical scanner. Data acquisition used a 3D stack‐of‐spirals trajectory, with undersampling along both the in‐plane and the through‐plane directions. The effect of B1 + inhomogeneity was accounted for by matching the acquired fingerprint to a dictionary simulated with the B1 + factors measured from a separate scan. In vitro and ex vivo studies were performed to evaluate the accuracy and the undersampling capacity of the MRF method. The application of the MRF method for in vivo, brain‐wide T1 and T2 mapping was demonstrated on macaques at 4, 6, and 12 years of age. Results: The MRF method enabled highly repeatable T1 and T2 mapping at high spatial resolution (0.35 × 0.35 × 1 mm 3 ) with an acceleration factor of 24. In vivo studies showed significant age‐related T2 reduction in deep gray nuclei including the globus pallidus, the putamen, and the caudate nucleus. Conclusions: This study demonstrates the first MRF study for brain‐wide, multi‐parametric quantification in non‐human primates with sub‐millimeter resolution.